A polydopamine-gated biodegradable cascade nanoreactor for pH-triggered and photothermal-enhanced tumor-specific nanocatalytic therapy. Issue 37 (15th September 2021) - Chen, Fanghui; An, Peijing; Liu, Ling; Gao, Zhiguo; Li, Yaojia; Zhang, Yuchen; Sun, Baiwang; Zhou, Jiancheng
Abstract : We report a pH-triggered cascade nanoreactor that could locally boost oxidative stress via increasing ˙OH generation and GSH depletion, showing great potential in tumor-specific nanocatalytic therapy. Abstract : Despite the great potential of cascade catalytic reactions in tumor treatment, uncontrolled catalytic activities in vivo lead to inevitable off-target toxicity to normal tissues, which greatly hampers their clinical conversion. Herein, an intelligent cascade nanoreactor (hMnO2 -Au@PDA, hMAP) was constructed by depositing glucose oxidase (GOx)-mimicking ultrasmall gold nanoparticles (Au NPs) into honeycomb-shaped manganese oxide (hMnO2 ) nanostructures and then coating them with polydopamine (PDA) to achieve pH-responsive and photothermal-enhanced nanocatalytic therapy. Upon exposure to the mild acidic tumor microenvironment (TME), the PDA gatekeeper would collapse, and the inner hMnO2 could simultaneously deplete glutathione (GSH) and generate Mn 2+, while a considerable amount of H2 O2 produced from the oxidation of glucose by GOx-mimicking Au NPs could accelerate the Mn 2+ -mediated Fenton-like reaction, yielding sufficient highly toxic ˙OH. More importantly, the pH-responsive cascade reaction between Au NPs and hMnO2 could be further enhanced by localized hyperthermia induced from PDA under near-infrared (NIR) laser irradiation, thereby inducing significant cell apoptosis in vitro and tumor inhibition in vivo . This work provided a promising paradigm by innovatively designing a TME-responsive and photothermal-enhanced cascade catalytic nanoreactor for safe and efficient cancer therapy.